The influence of environmental stability and upwelling variation on copepod diversity in the Humboldt Current System off Chile - Pérez-Aragón, Manuela; Rivera, Reinaldo; Oerder, Vera; González, Carolina E.; Hernández, Cristián E.; Escribano, Ruben (Frontiers in Ecology and Evolution, 2025)
The Humboldt Current System (HCS) is a highly dynamic upwelling system implying a strongly variable environment for zooplankton inhabiting the coastal zone. This variability has major consequences for population dynamics, community composition, and ultimately diversity patterns of planktonic copepods which dominate the bulk of zooplankton biomass. In this work, we tested the hypothesis that environmental stability is the key modulating mechanism of copepod diversity patterns in the HCS. We used a 17-years (1995-2011) database on species occurrence of copepods along with environmental data for the upper 500 m of the ocean (divided into five vertical strata) for the upwelling zone off Chile, distinguishing two regions (northern and southern) having different seasonal regimes of wind-driven upwelling. We estimated indices for copepod diversity and their distribution, segregated by regions and depth strata. The indices were then associated with oceanographic variables forced by upwelling intensity, along with an estimate of eddy kinetic energy (EKE), as a proxy of environmental stability. From the entire community, we found 18 dominant species widely distributed in the study area. Some were exclusive species for the upper depth stratum with differences in the number of exclusive species per region and depth. From Linear Mixed Models we found that the diversity indices significantly differed between regions and strata, and their variance was mainly explained by temperature, salinity, oxygen concentration, temperature stability, and eddy kinetic energy (EKE). Both temperature stability and EKE were the best predictors of copepods diversity, suggesting that climate-oceanographic stability, forced by upwelling intensity, is the key driver for promoting and maintaining copepod diversity in the HCS.